Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2340/16501977-2500
|View full text |Cite
|
Sign up to set email alerts
|

System complexities affecting recovery after a minor transport-related injury: The need for a person-centred approach

Abstract: Injuries from transport accidents are heterogeneous and recovery processes complex and challenging for people, regardless of the severity of injury sustained. Multiple factors influence the recovery trajectory, including pain, poor pre-accident health state, psychological comorbidities, socioeconomic disadvantage and, in some instances, financial compensation. In particular, the results on the effect of financial compensation on health outcomes following musculoskeletal injury remain controversial, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…We do not know if our results would be applicable to a wider non-compensable injured population or to patients managed by other compensation agencies, hence caution is advised when generalizing these findings. Thirdly, this study is limited to the analysis of the association between variables available in the current survey, and many other factors identified through previous qualitative study were not tested (32). Finally, the EQ-5D-3L was the only validated instrument in this study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We do not know if our results would be applicable to a wider non-compensable injured population or to patients managed by other compensation agencies, hence caution is advised when generalizing these findings. Thirdly, this study is limited to the analysis of the association between variables available in the current survey, and many other factors identified through previous qualitative study were not tested (32). Finally, the EQ-5D-3L was the only validated instrument in this study.…”
Section: Discussionmentioning
confidence: 98%
“…A recent systematic review (15) and qualitative study (16) provided the basis for selecting risk factors associated with poor recovery, to be tested in this study. The qualitative study sampled people contributing to the TAC COS, also used in this study.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…É notório que o acidente é visto como um evento inesperado, em que as pessoas não acreditam que possam acontecer consigo ou com pessoas próximas. A ideia prevalente, semelhante a outros achados, é que se trata de um evento distante, o que faz com que a segurança seja colocada em segundo plano 24 .…”
Section: Discussionunclassified
“…Psychological health appears to be the most adversely affected (Collie, 2018; Elbers et al, 2013; Murgatroyd et al, 2015b; Murgatroyd, Harris, Tran, & Cameron, 2016), as shown in a meta-analysis of 29 studies (Murgatroyd et al, 2015b), resulting in serious clinical and financial concern as psychological distress means delayed recovery and higher costs (Gopinath et al, 2019; Guest, Tran, Gopinath, Cameron, & Craig, 2017; Kenardy, Heron-Delaney, Warren, & Brown, 2015). Some have argued that secondary gain such as financial incentives (Cameron et al, 2008; Cassidy et al, 2000; Elbers et al, 2013; Hadler, 1996; Harris et al, 2005), or stressful claim processes or secondary victimization (Elbers et al, 2013; Grant et al, 2014; O'Donnell et al, 2015; Samoborec, Ayton, Ruseckaite, Winbolt, & Evans, 2019; Thompson, Elbers, Cameron, Craig, & Guest, 2018) may be responsible for poor outcomes among those seeking compensation. Nonetheless, the commonly held view that compensation is more harmful than helpful to health when engaged in compensation continues to have profound implications in terms of barriers to healthcare and stigmatization of compensation seekers (Grant & Studdert, 2009; Varker, Creamer, Khatri, Fredrickson, & O’Donnell, 2018).…”
Section: Introductionmentioning
confidence: 99%